Silver Triflate Catalyzed Synthesis of Isoquinolino[2,1-a]quinazolino[3,2-c]quinazoline Derivatives via Alkyne Hydroamination - Pan, Wan-Chen; Zhang, Mei-Mei; Liu, Jian-Quan; Wang, Xiang-Shan (Synthesis, 2019)
Using 2-(2-aminophenyl)quinazolin-4(3H)-one and 2-(2-phenylethynyl)benzaldehyde as the reactants, silver triflate (AgOTf) was proved to be an efficient catalyst to promote not only quinazoline cyclization, but also the intramolecular hydroamination of alkyne for the synthesis of 6-aryl-17H,18aH-isoquinolino[2,1-a]quinazolino[3,2-c]quinazolin-17-one derivatives in high yields.
Keywords: isoquinoline; quinazoline; hydroamination; AgOTf; synthesis